Pengaruh Partisipasi Anggaran Dan Asimetri Informasi Terhadap Senjangan Anggaran Pada Satuan Kerja Perangkat Daerah (SKPD) Provinsi Sumatera Barat - Gerry Hamdani Putra; Adrianto Gidion Gulo (BADAN PENERBIT STIEPARI PRESS, 2024)
This research aims to determine: 1. To determine the effect of budget participation on the budget gap in the Regional Work Units (SKPD) of West Sumatra Province; 2. To determine the effect of information asymmetry on the budget gap in the Regional Work Units (SKPD) of West Sumatra Province; The method used in this research is a quantitative method with a descriptive approach. The sample in this study was 72 respondents with a sampling technique using purposive sampling. The data analysis technique used is multiple linear regression analysis using SPSS 26. Data analysis techniques start from validity testing, reliability testing, normality testing, heteroscedasticity testing, multicollinearity testing, multiple linear regression analysis, and hypothesis testing. This research shows the results: 1) Budget participation has a positive and significant effect on the budget gap with a calculated t-value greater than the t-table (2.480>1.667) with a significant value smaller than the alpha value (0.016<0.05); 2) Information asymmetry has a positive and significant effect on the budget gap with a calculated t-value greater than the t-table (2.567<1.667) with a significant value smaller than the alpha value (0.012<0.05).